2022
DOI: 10.21897/rmvz.2387
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedades bacterianas y sus agentes etiológicos identificados en peces de México - Una Revisión

Abstract: Este trabajo concentra la información bibliográfica existente acerca de las bacterias aisladas y/o identificadas a partir de peces de México. El análisis muestra que el estudio de la sanidad de peces del país es relativamente reciente, y describe el aislamiento de varios géneros bacterianos obtenidos tanto de peces clínicamente enfermos como subclínicos, con alta frecuencia de bacterias oportunistas; asimismo se muestra que en la última década se ha confirmado la presencia de bacterias emergentes causando enfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Batches with positive results to A. hydrophila showed coincidences with the symptomatology described ty Fuentes and Pérez (1998), who linked the presence of the bacteria to exophthalmos, darkening of the skin, altered behaviour pattern, 80% sickness rate, and a 52% death rate. Nevertheless, these visual symptoms match other pathogens that also attack trouts (Alcántara-Jauregui et al, 2022). However, the PCR technique has a 97.5% accuracy and the results regarding the presence of this bacteria can be therefore considered trustable (Chapela et al, 2018).…”
Section: Pcr Test For the Detection Of Aeromonasmentioning
confidence: 84%
See 1 more Smart Citation
“…Batches with positive results to A. hydrophila showed coincidences with the symptomatology described ty Fuentes and Pérez (1998), who linked the presence of the bacteria to exophthalmos, darkening of the skin, altered behaviour pattern, 80% sickness rate, and a 52% death rate. Nevertheless, these visual symptoms match other pathogens that also attack trouts (Alcántara-Jauregui et al, 2022). However, the PCR technique has a 97.5% accuracy and the results regarding the presence of this bacteria can be therefore considered trustable (Chapela et al, 2018).…”
Section: Pcr Test For the Detection Of Aeromonasmentioning
confidence: 84%
“…In Mexico, the Servicio Nacional de Sanidad, Inocuidad y Calidad Agroalimentaria (SENASICA) is in charge of following up epizootic diseases in aquaculture. However, scarce information has been published about the introduction or outbreak of pathogen bacteria in trouts (Alcántara-Jauregui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas are found naturally in aquatic, terrestrial, and atmospheric environments, as well as being part of the intestinal microbiota of healthy fish (Balbuena and Rios, 2011;Puello-Caballero et al, 2018;Alcántara-Jauregui et al, 2022). However, Pseudomonas can cause infection in fish (Ardura et al, 2013;Kačániová et al, 2017) known as Pseudomonadiasis which is septicemic in fish that live in fresh and brackish waters (Balbuena and Rios, 2011;Puello-Caballero et al, 2018;Alcántara-Jauregui et al, 2022).…”
Section: Animal Health: Fish and Pseudomonasmentioning
confidence: 99%
“…In aquaculture activities, processes such as the management of individuals, batch classification, application of cleaning procedures, use of chemical products, inadequate culture density and water quality, poor nutrition, transport between facilities, or alteration of environmental conditions can generate a state of stress in fish, favoring infection and disease outbreaks by various causal agents, including Pseudomonas (Balbuena and Rios, 2011;Bautista Covarrubias et al, 2011;Ardura et al, 2013;Cepa et al, 2019;Duman et al, 2021). Within the genus, P. aeruginosa, Pseudomonas anguilliseptica, P. baetica, P. chlororaphis, P. fluorescens, P. koreensis, P. luteola, P. plecoglossicida, P. pseudoalcaligenes and P. putida have been reported to cause disease in several species of fish (Austin et al, 2007;Duman et al, 2021;Alcántara-Jauregui et al, 2022). Conducted studies have reported almost a 100% mortality from infection with Pseudomonas spp., fish such as sea bream, sea bass, Ayu, and rainbow trout in aquaculture conditions (Duman et al, 2021).…”
Section: Animal Health: Fish and Pseudomonasmentioning
confidence: 99%
“…In 2020, the Ministry of Agriculture and Rural Affairs of China classified streptococcosis as a contagious invasive disease (Class II) due to its severity [ 23 ]. Recent outbreaks of this infection were documented in aquaculture farms in Brazil and Mexico [ 24 , 25 ]. Although it is a significant pathogen in aquaculture, recent research has reported streptococcosis presence caused by this bacterium in marine mammals and fish, indicating that it could pose a risk to wild populations [ 26–29 ].…”
Section: Introductionmentioning
confidence: 99%